TRANSLOCATIONS OF PSYCHOANALYSIS (Review article) - Kometsi, Kgamadi (PINS-Psychology in Society, 2025)
INITIAL RESPONSES TO THE BOOK. In the introduction to his book, Japan in analysis (2008), Ian Parker relates an experience he had at a barbershop at informing the barber that he will be writing a book on Japan and psychoanalysis. For the barber, the idea that anyone would want to write about Japan and psychoanalysis is so inconceivable that he is thrown into uncontrollable laughter at hearing this. In what is likely to have been a derisive attempt to picture what the book might be about, he in fact, manages to capture the essence of its structure, as Parker says. This would be the one level at which the barber’s astonishment that someone could be planning to write a book about Japan could be read. A different and somewhat deeper meaning emerges when one links this inquiry with the one appearing later on in the book, of a participant asking, “why are you asking these questions”. Part of what this book seems to raise is a question as to what it is about Japan that warrants writing a book on psychoanalysis. I would suggest that an even more complex question is engendered in these enquiries, about power relations resident in positions of object and subject.